Legal Case-Based Reading to Promote Critical Thinking for Law Students - Misnawati Misnawati; Zul Astri; Reski Pilu (Graduate School of Universitas Negeri Malang, 2023)
Critical thinking and creativity are the essential qualities must-have to face industrial revolution 4.0 and society 5.0, particularly for students. Higher education institutions play a vital role in de-veloping critical thinkers. This study aimed to assess the impact of the author's teaching tech-nique of Legal Case-based Reading (LCbR) on students' critical thinking abilities. This study used a quantitative approach with collecting data through observations, doing a pre-test, treat-ment, post-test, and following by questionnaire to see how the students felt about the program. The data was then analyzed by using SPSS 26 program. The participants in this study are first-semester students at Sekolah Tinggi Ilmu Hukum Pengayoman Watampone, Indonesia, in the 2020/2021 academic year. Subjects were chosen using a purposive sampling strategy, with 43 samples. The research lasts for approximately two months, from September—November 2020. This research showed that (1) applying Legal case-based Reading has a considerable effect and change on students' critical thinking skills; (2) students' critical thinking level increased from low order thinking skills to high order thinking skills, and (3) Students thought the response options were good, with an average value is in the